Application of as-synthesised MCM-41 and MCM-41 wrapped with reduced graphene oxide/graphene oxide in the remediation of acetaminophen and aspirin from aqueous system. (1st March 2018) - Akpotu, Samson O.; Moodley, Brenda
Abstract: In this study, ASM41 (as-synthesised MCM-41), MCM-41, MCM-41 encapsulated with graphene oxide (MCM-41-GO) and reduced graphene oxide (MCM-41-G) were fabricated and utilized in the remediation of acetaminophen and aspirin from water. A surfactant template (cetyltrimethylammonium bromide) was added to ASM41 to make it more hydrophobic and its effects on the remediation of acetaminophen and aspirin from wastewater was studied. To further improve the adsorption capacity of the adsorbent, MCM-41 was encapsulated with GO and G which also aided in easy separation of the adsorbent from the aqueous solution. Comparative studies of the adsorption of acetaminophen and aspirin on all four adsorbents were investigated. Batch adsorption studies of acetaminophen and aspirin were carried out to determine the effects of pH, initial concentration, time and adsorbent dose. Adsorption mechanism was through EDA, π-π interactions, and hydrophobic effects. Data from sorption kinetics showed ASM41 had the highest qm value for aspirin (909.1 mg/g) and MCM-41-G had the highest qm value for acetaminophen (555.6 mg/g). The significant adsorption by ASM41 can be attributed to increased hydrophobicity due to the retention of the surfactant template. Thermodynamic studies revealed the adsorption process as spontaneous and exothermic. Desorption studies revealed that adsorbents could be regenerated and reused for adsorption. Graphical abstract: Image 1 Highlights: Novel as-synthesised MCM-41, MCM-41 encapsulated graphene oxide/reduced graphene were fabricated. Adsorbents were applied to remove acetaminophen and aspirin from simulated and real wastewater. Adsorption followed the pseudo-second order, Freundlich and Langmuir models. Adsorption mechanism was explained. Adsorbents were easily regenerated after adsorption with high removal efficiency.